2022
DOI: 10.3233/jad-210565
|View full text |Cite
|
Sign up to set email alerts
|

Physician Diagnosis and Knowledge of Mild Cognitive Impairment

Abstract: Background: Older adults with mild cognitive impairment (MCI) receive fewer guideline-concordant treatments for multiple health conditions than those with normal cognition. Reasons for this disparity are unclear. Objective: To better understand this disparity, we describe physician understanding and experience with patient MCI, particularly physician identification of MCI, ability to distinguish between MCI and dementia, and perspectives on education and training in MCI and dementia. Methods: As part of a mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Despite the key importance of early identification of MCI, there are substantial obstacles to its timely diagnosis. This is mostly due to the limited time of practitioners for screening and because the value of MCI’s early detection is not completely clarified among the clinicians 8 , 9 . Moreover, many of the affected people believe that their early symptoms are due to aging, and they only visit their doctors once symptoms are getting worse.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the key importance of early identification of MCI, there are substantial obstacles to its timely diagnosis. This is mostly due to the limited time of practitioners for screening and because the value of MCI’s early detection is not completely clarified among the clinicians 8 , 9 . Moreover, many of the affected people believe that their early symptoms are due to aging, and they only visit their doctors once symptoms are getting worse.…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that this lack of confidence will pose an even greater obstacle to cardiologists without special interest in geriatric cardiology. It is not surprising that cardiologists do not feel confident to perform cognitive screening, since physicians, in general, are not sufficiently trained to recognize cognitive problems in their patients 17 . A previous study showed that the number of cognitive problems perceived by physicians through clinical impression significantly lags behind the number of objectively assessed cognitive impairments 18 .…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that cardiologists do not feel confident to perform cognitive screening, since physicians, in general, are not sufficiently trained to recognize cognitive problems in their patients. 17 A previous study showed that the number of cognitive problems perceived by physicians through clinical impression significantly lags behind the number of objectively assessed cognitive impairments. 18 In the event of vascular cognitive impairment, this difference may be due to symptoms like slowed thinking and apathy, which can be less evident to clinicians than typical hallmarks of Alzheimer disease like memory loss.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Such an active-control design might help for more robust comparison as compared with previous placebo-controlled studies 36. Second, this study focuses on a non-pharmacological intervention for mild cognitive decline in older patients with hypertension, which is important for the patients’ well-being but often overlooked by cardiologists in daily clinical practice 37. Finally, this study will be the first to adopt advanced neuroimaging technology of ultra-high field MRI (7.0 T) to assess the changes in the brain after cognitive training in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%